ІМІТАЦІЙНО-ІГРОВИЙ ПІДХІД ЯК ОСНОВА ТЕХНОЛОГІЇ ПІДГОТОВКИ МАЙБУТНІХ ПЕДАГОГІВ ДО ТВОРЧОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2001)
This article deals with playing technologies in students’ preparing to their professional activity. The author shows the advantage of imitative-playing teaching in activization of training work and development o f creative abilities of teachers to come.